Determination of the Hot Rolling Stress by Means of Tensile Tests [Determinación de la Tensión de Laminación en Caliente a Partir de Ensayos de Tracción] - Monsalve-Gonzalez, A; Artigas-Abuin, A (2013)
Prediction of mechanical behavior of hot rolled steels is an important aspect during industrial processing. The rolling stress needed to the process were estimated using three methods, the first of which is related to the Sellars?s model that takes into account the friction coefficient and the yield stress. The second method estimates the rolling stress as the average stress obtained during the tensile tests. The third method, estimates the rolling stress from the data of power consumed by the rolling equipment. This methodology was applied in this study to a carbon steel. The conclusion of the work is that results obtained by Sellars?s and consumed power, are coincident. The method based on the average tensile stress predicts stresses lower than those obtained with other two methods.